Novel associations among insect herbivores and trees: Patterns of occurrence and damage on pines and eucalypts - Stazione, Leonel Daniel (2025)
Globalization has led to a significant increase in the establishment of forest plantations with exotic species and to the accidental introduction of forest insects worldwide. Cumulatively, these factors contribute to the increased occurrence of novel associations between phytophagous insects and trees, leading to new interactions between species that have not historically co-occurred. Here, we reviewed the patterns of novel associations between herbivorous insects and pines and eucalypts at a global scale and identified factors that could favor the occurrence of novel associations and their impacts on forestry. We recorded 766 novel associations of insects with pines and 356 with eucalypts, involving 852 species of herbivorous insects. Most of the novel associations occurred in the Neotropic, Austro-Pacific, and Palearctic regions. In all biogeographic regions, novel associations involved mostly native insects on exotic trees, except for the Nearctic, where exotic insects were dominant. Generalist insects were more frequently involved in novel associations, but specialist ones caused higher damage levels. Foliage feeders and wood and phloem feeders were the most frequent feeding guilds involved in new associations, while sap feeders, shoot feeders, and fruit and seed feeders were rare. For pines, non-native insects were more frequently associated with trees phylogenetically related to hosts in their native range, and native insects were more frequently associated with unrelated hosts. However, for both exotic and native insects, novel associations with eucalypts primarily involved hosts that are unrelated to hosts in their native range. The significance of extensive forest plantations with non-native species and the biogeographic context are emphasized as factors associated with the occurrence of novel associations between insects and trees. This study highlights the importance of international collaboration in forest insect monitoring and surveillance programs to facilitate the early detection of novel associations as an important first step toward minimizing their impact.